The Prevention of Sexual Violence Against Women Based on Minangkabau Local Wisdom - Fithri, Widia; Yulika, Febri; Ermagusti, Ermagusti (UIN Sunan Kudus, 2022)
This paper aims to explain the local wisdom used in preventing sexual violence against women in West Sumatra Province. This type of research uses a PAR approach through management planning, actuating, organizing, and reflecting. Data were analyzed descriptively using data reduction, display, and verification. The findings of this study show that Aisiyah organization used the local wisdom to change people’s mindsets in seeing victims of sexual violence as figures that need to be strengthened together. The Minangkabau traditional order, which is based on customs and religion, is a comprehensive guide to governing people’s lives, particularly in the Minangkabau community. Minangkabau customs’ philosophical values of adat basandi syarak-syarak basandi kitabullah place women to a noble position. Women are the limpapeh rumah nan gadang, or the pillars of rumah gadang, which symbolize honor and glory. Women, as bundo kanduang, become symbols both physically and personality because they know how to behave in good manners and how to dress appropriately.